Improvement in thermal shock resistance of gadolinium zirconate coating by addition of nanostructured yttria partially-stabilized zirconia. Issue 6 (July 2015) - Zhong, Xinghua; Zhao, Huayu; Liu, Chenguang; Wang, Liang; Shao, Fang; Zhou, Xiaming; Tao, Shunyan; Ding, Chuanxian
Abstract: Gadolinium zirconate (Gd2 Zr2 O7, GZ) as one of the promising thermal barrier coating materials for high-temperature application in gas turbine was toughened by nanostructured 3 mol% yttria partially-stabilized zirconia (YSZ) incorporation. The fracture toughness of the composite of 90 mol% GZ-10 mol% YSZ (GZ–YSZ) was increased by about 60% relative to the monolithic GZ. Both the GZ and GZ–YSZ composite coatings were deposited by atmospheric plasma spraying on Ni-base superalloys and then thermal-shock tested under the same conditions. The thermal-shock lifetime of GZ–YSZ composite coating was improved, which is believed to be mainly attributed to the enhancement of fracture toughness by the addition of YSZ. In addition, the failure mechanisms of the thermal-shock tested GZ–YSZ composite coatings were discussed.